2023
DOI: 10.1021/acscentsci.2c01522
|View full text |Cite
|
Sign up to set email alerts
|

Conserved Protein–Polymer Interactions across Structurally Diverse Polymers Underlie Alterations to Protein Thermal Unfolding

Abstract: Protein−polymer conjugates are widely used in many clinical and industrial applications, but lack of experimental data relating protein−polymer interactions to improved protein stability prevents their rational design. Advances in synthetic chemistry have expanded the palette of polymer designs, including development of nonlinear architectures, novel monomer chemical scaffolds, and control of hydrophobicity, but more experimental data are needed to transform advances in chemistry into next generation conjugate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…Following bioconjugation, purification is essential due to free or unconjugated polymers causing unintended effects that may be unaccounted by researchers. 44 Techniques for purification include chromatography, 38,45,46 dialysis, 47,48 and filtration 49 to remove unreacted polymer. Methods to confirm soluble protein-polymer bioconjugation synthesis primarily rely on observing an increased apparent molecular weight to unmodified proteins.…”
Section: Synthesis Of Soluble Protein-polymer Bioconjugatesmentioning
confidence: 99%
See 2 more Smart Citations
“…Following bioconjugation, purification is essential due to free or unconjugated polymers causing unintended effects that may be unaccounted by researchers. 44 Techniques for purification include chromatography, 38,45,46 dialysis, 47,48 and filtration 49 to remove unreacted polymer. Methods to confirm soluble protein-polymer bioconjugation synthesis primarily rely on observing an increased apparent molecular weight to unmodified proteins.…”
Section: Synthesis Of Soluble Protein-polymer Bioconjugatesmentioning
confidence: 99%
“…Biomaterials Science to map galectin-polymer interactions of linear and nonlinear PEG conjugated to galectin. 45 Stability. Protein stability is intrinsically linked to tertiary and secondary structure and therefore function.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Of particular importance are enzyme–polymer, polymer–polymer, and polymer–solvent interactions, which may be driven by a combination of hydrophobic, hydrogen bonding, electrostatic, and steric effects. For example, previous studies have shown that enzyme–polymer interactions may influence enzyme activity via effectively mediating substrate binding. , Additionally, protein solubility , and stability can also be dramatically impacted by protein–polymer interactions. , Interestingly, the addition of soluble random heteropolymers that are chemically diverse has also been shown to dramatically increase enzyme stability through a chaperone-like mechanism . This approach was specifically demonstrated for a broad range of structurally diverse enzymes, including horseradish peroxidase, glucose oxidase, and organophosphorus hydrolase.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the understanding of how these properties may be intentionally manipulated to modulate protein function remains poorly understood. Importantly, polymer–polymer interactions may also impact protein behavior ,, as neighboring chains begin to interact with one another, or fold back on themselves, creating a distinctive polymer-defined niche. For example, the formation of collapsed zwitterionic polymer mats through ion pairing can significantly change the polymer hydration layer .…”
Section: Introductionmentioning
confidence: 99%